2006
DOI: 10.1007/s11910-996-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness and unintended sleep in Parkinson’s disease

Abstract: Patients with Parkinson's disease and parkinsonian syndromes (eg, dementia with Lewy body disease, multisystem atrophy, and Shy-Drager syndrome) suffer from daytime sleepiness. This sleepiness is common and very real, often approaching levels observed in the prototypical disorder of sudden-onset sleep, namely narcolepsy/cataplexy. Physicians need to be vigilant in assessing parkinsonian patients for sleepiness because treatment can dramatically enhance quality of life and prevent the significant morbidity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 77 publications
0
30
0
3
Order By: Relevance
“…Previous studies have shown an impact of levodopa and dopamine agonists on EDS in PD [3,6,7]. Dopaminergics may exacerbate sleepiness in a subset of patients in a dose-dependent fashion [28]. There might be an individual susceptibility to specific antiparkinsonian drugs, which may play a role in the etiology of sleepiness in PD patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an impact of levodopa and dopamine agonists on EDS in PD [3,6,7]. Dopaminergics may exacerbate sleepiness in a subset of patients in a dose-dependent fashion [28]. There might be an individual susceptibility to specific antiparkinsonian drugs, which may play a role in the etiology of sleepiness in PD patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Bupropion, an antidepressant that increases synaptic dopamine by blocking the dopamine transporter, may be useful not only in improving depression in patients with PD but also in improving daytime alertness [ 42 ]. Quetiapine, an antipsychotic drug that has fewer extrapyramidal effects than older antipsychotics, is effective for treating psychosis and hallucinations allowing more restful nocturnal sleep [ 43 ].…”
Section: 7mentioning
confidence: 99%
“…Since this report, sleepiness in PD has been critically reappraised and EDS is common [10,11] [12]. Sudden daytime sleep episodes that occur without warning ("sleep attacks") are also associated with DAs [9][10][11][12][13] [14][15][16][17] [29][30][31][32][33].…”
Section: Dopaminergics and Excessive Daytime Sleepinessmentioning
confidence: 99%